Exploring Sustainability Agency and Hope at Four United World Colleges through an Emergent Complex Systems Lens - Raj, Ann (My University, 2024)
This exploratory research thesis investigates United World College (UWC) students' self-perceived action competence for sustainability and their hope for the future. The study explores potential associations between established scales, namely the Self-Perceived Action Competence for Sustainability (SPACS) scale by Olsson et al. (2020) and the Environmental Action Scale (EAS) developed by Alisat & Reminer (2015), as well as two researcher-developed scales focusing on sustainability knowledge and the contribution of UWC education to students' sense of hope and self-reported ability to act for sustainability. Grounded in an emergent complex systems perspective, the research views UWC schools as socio-technical systems within which student-learner agents operate. The study did not find statistically significant associations between the scales and hope for the future. This suggests a nuanced understanding among students regarding their feelings and perceptions about the future in the context of sustainability and transitions towards more sustainable practices. This research contributes to ongoing discussions on the role of youth education in fostering sustainability transitions and provides insights into the complex interplay between individual agency, educational experiences, and hope within a global educational context like UWC.
Keywords: Hope, Agency, Action Competence, Education for Sustainability, International Baccalaureate, Environmental Education, United World College Movement, Sustainability transitions.